The Equilateral Agility Concept as Mediating Variable in Relationship between IT-Strategy Alignment and Sustainable Competitive Advantage - Nurcholis, Lutfi; Cahyono, Budhi (JDM (Jurnal Dinamika Manajemen), 2019)
This paper aims to investigate the effect of IT-strategy alignment, responsiveness, operational flexibility, and business relationship on sustainable competitive advantage and the mediating effect of responsiveness, operational flexibility, and business relationship in relationships between IT-strategy alignment and sustainable competitive advantage. Data were collected from 189 Batik SME in Pekalongan and analyzed by using Structural Equation Modeling (SEM). The result shows that IT-strategy alignment significantly affects responsiveness. Responsiveness, operational flexibility, and also business relationship significantly affect sustainable competitive advantage. Furthermore, responsiveness, operational flexibility, and business relationship mediate the correlation of IT-strategy alignment and sustainable competitive advantage. Responsiveness, operational flexibility, and business relationship have the confidence and value that puts customers on every business decision. It encourages Batik SME to improve the sustainable competitive advantage based on the customers’ expectations. IT-strategy alignment is essential to enhance responsiveness, operational flexibility, and business to gain a sustainable competitive advantage. That IT-strategy alignment can improve the sustainable competitive advantage of the Batik SME.